Application of Six Sigma DMAIC Methodology to Reduce Medication Errors in a Major Trauma Care Centre in India - George, Ankitha; Joseph, Aida Mary; Kolencherry, Sreenath; Kodath, Vishnu Vettekkaram; Menaka, Kaliyan; Duraisingh, Britto; Haja Sherief, Sheik; Shivakumar, Thangavel (Indian Journal of Pharmacy Practice)
Introduction: Medication error is a continuing global phenomenon. It is an important public health problem that poses a serious threat to patient safety. This study was carried out to analyze the effect of Six Sigma methodology in reducing medication errors in a tertiary care hospital. Method: A Prospective study on application of Six Sigma DMAIC methodology to reduce medication errors were conducted during a period of February 2017 to July 2017 at Ganga Medical College Hospital, Coimbatore, Tamil Nadu. Results: Out of 1050 cases, the number of prescribing, transcribing, dispensing, administering and monitoring errors were found to be 62, 19, 6, 47 and 14 in the measure phase which reduced to 12, 10, 2, 7 and 4 in the improve phase. Conclusion: Implementation of DMAIC methodology showed a marked reduction in medication errors, correspondingly the sigma value improved from 3.56, 3.93, 4.33, 3.63 and 4.1 to 4.15, 4.16, 4.66, 4.33 and 4.33. Regular auditing and proper follow up can result in sustaining the improvement in the medication use process.
Keywords: Six Sigma; Medication errors; Adverse drug events; Error outcome category.